Report on the 44th International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2021) - Shah, Chirag; Suel, Torsten; Diaz, Fernando; Mitra, Bhaskar; Poblete, Bárbara; Suleman, Hussein; Verberne, Suzan (SIGIR Forum, 2022)
ACM SIGIR 2021 conference was organized as a fully online event, with more than 1,000 attendees from dozens of countries, a large technical program, and several activities and initiatives not seen at SIGIR before. This conference report provides some of the important details of how the organizers navigated through changing environments – political, social, and public health – moving the conference from NYC to Montreal and then to online. In addition to that decision process, the report also highlights several new and renewed initiatives around diversity, equity, and inclusion (DEI). Written by the conference General Co-Chairs and the DEI Chairs, this report is meant to inform future conference organizers as well as the SIGIR community at large.